Innovative experience of the ontological structuring of knowledge with teachers and students - Londoño Palacio, Olga Lucía; Calderón Villafáñez, Liccy Catalina; Lucumí Useda, Paola; González Castañeda, Martha Alexandra (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The objective of this article is to evaluate the effect of the incorporation of the Marcos System for Significant Learning (SIMAS) software in teaching practices in two educational institutions, Escuela Normal Superior de Ubaté, ENSU and Fundación de Educación Superior Nueva América, FESNA. The methodological approach was of a mixed nature, attending interviews, observations, logs and field notes from the qualitative perspective and perception surveys applied to teachers and students in the quantitative paradigm. The main results found that the incorporation of software in classes contributed positively in the processes of communication between teachers and students because their use was a change in the approach to teaching strategies related to the use of ICT favoring individual and collaborative work. Likewise, an increase was seen in the grounds of both actors to the process of learning, finding new ways to interact with each other and with the contents, also favoring the integration of different areas.